Just a song Chinese lyrics from the eleventh and early twelfth centuries - Owen, Stephen 1946- (Harvard-Yenching Institute monograph series, 2019)
"Analyzes the transformation of song lyric (ci), a form of Chinese poetry, from performance contribution to a full literary genre. Examines its discursive contrast to older classical poetry, as well as its emphasis on sensibility, which was lost in the new Song world of righteousness and public advancement"...Provided by publisher